Relações de gênero no currículo da educação infantil: a produção das identidades de princesas, heróis e sapos - Danielle Lameirinhas Carvalhar (2009)
The objective of the present research is to analyze how a childlike education curriculum, in a municipal school in Belo Horizonte city, has contributed to nominate and produce gender identities of the infants attended. For the analyses achievement, had been used as theoretical reference the gender studies and the contributions of cultural studies, based on the post-structuralism approach. Through methodological procedures inspired in ethnography, and using different concepts as gender, curriculum, identity, power and others, this dissertation analyzes the ways like masculinities and femininities are produced in the investigated curriculum. The argument developed in this dissertation is that the investigated curriculum invests repeatedly on the childlike identities presenting the femininities and masculinities standards models and its marks broadly divulged and accepted in our society, as the norm to be followed in its behaviors. To have these desirable identities in fact produced, it is utilized various strategies in order to guarantee the control about the sexuality of the infants, their bodies and to discipline their conducts. Throughout this dissertation, it is shown how the divulged discourses in the curriculums investigated teach to infants how they should proceed, be dressed and behave, to whom and how they must obey in order to have concrete effects in the production of the demanded identities. The analysis shows that, by means of differentiated power techniques, behaviors considered adequate to a good conduct for each gender are taught to the children. In that trial, gender crosses to other categories as sexuality, body, race and power so that the boys and girls identities can be produced. Regarding the sexuality, heteronormatives discourses are request in the attempt to produce the heterosexuality as social norm and to regulate the childrens behavior, by constraint, censorship and stimulation of the norms. Regarding the bodies, the analysis also shows how the discourses circulate in the family and media crossing with the curriculum discourse to produce the males and females as differentiated forms of childlike bodies, with important implications in its gender identities. In what refers to race, the study shows that the gender identities are crossed by ethnic-racial questions, here analyzed like another identity marker with significant effects in the production of a certain kind of children. The articulation of the gender and race representations, present in the investigated curriculum, shows how the exaltation of the white skin color causes different effects in the production of boys and girls. Finally, this study samples that, in the studied curriculum, discipline power techniques appears to control childhood, being more and more perceptible the trespass of the contemporary infancy to the norms imposed by school, as regarding the boys, considered undisciplined, and regarding the girls, seen as obedient, differently than some contemporary studies show. However, despite all the investment to normalize the children in standards such as gender behaviors, its constituents effects are not completely guaranteed because there is, in the interior of the discourse, conflicts, disputes, escapes, resistances and negotiations in what is taught by the curriculum for the production of childlike gender identities meanings. In this direction, the study shows that it is always possible to construct new manners of being and act regarding to the genders.